Answer:
The property of equality that justifies going from the first statement to the second statement is;
Subtraction property of equality
Explanation:
The given equation is presented here as follows;
AB + BC = 42
AB = 42 - BC
The above equation can be simplified as follows;
AB + BC = 42
AB + BC - BC = 42 - BC
(+ BC - BC = 0)
Therefore, we have;
AB + BC - BC = AB + 0 = AB = 42 - BC
AB = 42 - BC which is the subtraction property of equality
For the subtraction property of equality, when we subtract a value from one side of the equation, we must subtract the same value from the side of the equation as follows
Given that the letters a, b, and c represent any numbers
When we have;
a = b
Then we also must have;
a - c = b - c